2016
DOI: 10.1186/s40880-016-0164-5
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II trial evaluating concurrent carbon-ion radiotherapy plus chemotherapy for salvage treatment of locally recurrent nasopharyngeal carcinoma

Abstract: BackgroundAfter definitive chemoradiotherapy for non-metastatic nasopharyngeal carcinoma (NPC), more than 10% of patients will experience a local recurrence. Salvage treatments present significant challenges for locally recurrent NPC. Surgery, stereotactic ablative body radiotherapy, and brachytherapy have been used to treat locally recurrent NPC. However, only patients with small-volume tumors can benefit from these treatments. Re-irradiation with X-ray—based intensity-modulated radiotherapy (IMXT) has been m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…To our knowledge, the question of whether the addition of concurrent chemotherapy to salvage IMCT can improve disease control further in patients with LR‐NPC after they fail definitive RT is unknown. This is the subject of one of the dose escalating trials that currently is ongoing at SPHIC …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, the question of whether the addition of concurrent chemotherapy to salvage IMCT can improve disease control further in patients with LR‐NPC after they fail definitive RT is unknown. This is the subject of one of the dose escalating trials that currently is ongoing at SPHIC …”
Section: Discussionmentioning
confidence: 99%
“…This is the subject of one of the dose escalating trials that currently is ongoing at SPHIC. 17 The use of Epstein-Barr virus (EBV) DNA as a prognosticator and to guide treatment has been a focus of investigation for patients with NPC. In a pivotal study published by Lin et al, 32 a higher pretreatment plasma EBV (pEBV) DNA concentration was found to be a significant predictor of worse outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The National Comprehensive Cancer Network currently recommended CCRT as the standard treatment for locoregionally advanced NPC and its survival benefits are well-demonstrated [7] , [9] , [10] , [20] , [21] , [22] , [23] , [24] . Over the last decade, much attention has been paid to assessment of the prognostic value of adding IC to CCRT in locoregionally advanced NPC [11] , [12] , [13] , [14] , [15] , [16] , [25] , [26] , as it may improve LRRFS, DMFS and OS. Though the results obtained are controversial, a meta-analysis of these trials conducted by Ouyang et al [16] indicated IC could effectively enhance OS and reduce distant metastasis in locoregionally advanced NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have been demonstrated the feasibility of reduced-dose radiotherapy based on IC, 11,18,26 reduced-dose radiation for newly diagnosed patients without metastasis may be overaggressive. 27 Therefore, reduced-dose radiotherapy for NPC should be approached with caution. 27 Therefore, reduced-dose radiotherapy for NPC should be approached with caution.…”
Section: Discussionmentioning
confidence: 99%